Metabolic acidosis as a consequence of maximal effort in female field hockey players in an annual training cycle - Podgorski, T.; Krysciak, J.; Pawlak, M.; Konarski, J.; Domaszewska, K. (Studies in Physical Culture and Tourism, 2011)
The goal of the study was to determine the influence of maximal physical effort on the acid-base balance in female field hockey players in a yearly training cycle. Twelve members of the National Polish Field Hockey Team were ested once in the preparatory and twice in the competitive period of one training macrocycle. Using a portable ergospirometry system, the athletes were examined on a motorized treadmill to determine their maximal oxygen uptake (VO2max) and ventilatory threshold (VT). Lactate (LA) concentration in capillary blood was assessed to calculate the intensity of physical effort and metabolic response. The biochemical parameters of acid-base balance were determined using a blood gas analyzer. Mean VO2max VT values indicated a medium level of the tested competitors` aerobic fitness. The highest VO2max and VT values were observed at the beginning of the competitive period. After each test, the lactate concentration was elevated, while pH, concentration of bicarbonate ions, and base excess rapidly decreased. All calculated differences in biochemical parameters measured at rest and post-exercise were highly significant. The lowest differences in pH and lactate concentration were observed in the mid-competitive period. Those biochemical changes showed that metabolic acidosis was present in all three examinations. The lowest acid-base balance disturbances were observed in the mid-competitive period.